(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Organizations and professionals are usually unaware about the fundamental rationale behind workplace ethnocentrism. Due to globalization today’s workplace are becoming multi-cultural, thus to address and understand the intricacies of ethnocentrism and being sensitive towards the issue is the need of the hour. Effective management of culturally diversified workplace is significant point of concern. As it may germinate challenges before the organization, one such challenge is related with ethnocentric feeling among culturally diversified workforce towards each other. This paper will explain the concept of ethnocentrism at workplace, the psychology of ethnocentric tendency and the various problems that an ethnocentric view presents before the multicultural organization while dealing with culturally diversified employees by synthesizing various research studies done in this area, comprising of examining various approaches to ethnocentric tendency. It also answers why diversity at workforce that exemplifies a changing world and contemporary workplace which is vital for creating competitive work environment that enhance work productivity. It will also discuss the implication of ethnocentrism in multicultural organizations and how to avoid the intricacies of ethnocentric phenomenon and resultant conflicts and disruptions arising at the workplace.